A water-based coating composition and preparation method thereof
By using a composition with hydraulanide polyurethane surface paint and hydrophilic oxygen paint on magnesium alloy substrates, combined with specific proportion and component design, the problem of insufficient adhesion, hardness and weather resistance among the existing technologies can be solved. The coating film with high adhesion, hardness and weather resistance meets environmental protection requirements.
Patent Information
- Application Number
- CN202410965517.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-07-18
AI Technical Summary
The prior art is difficult to form a water-based coating film with excellent adhesion, hardness and weather resistance on a magnesium alloy substrate, and the VOC content of traditional solvent-based coatings is difficult to meet environmental protection requirements.
The composition of hydraulanide polyurethane surface paint and water -based epoxy primer is used. It is designed by specific proportion and components, including hydroxyl acrylic decentralized, double -layer coated aluminum silver slurry, and modified fatty lipolymine curing agent. , Form coatings with excellent adhesion, hardness and weather resistance.
A coating film with strong adhesion, high hardness, alkali resistance and humidity resistance on magnesium alloy substrates, reduces the VOC content, meets environmental requirements, and improves the toughness of coating the coating film and reassembling performance.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water-based coatings, and in particular relates to a water-based coating composition and a preparation method thereof. Background Art
[0002] Currently, the notebook shells with magnesium alloy substrates on the market all use traditional solvent-based coatings, which have the defects of high VOC emissions and great impact on the human body. Usually, the VOC content of solvent-based coatings on the market is above 700g / L, while the VOC control requirements for solvent-based coatings for electronic and electrical coatings specified in GB30981-2020 are below 700g / L. As environmental protection requirements become increasingly stringent, existing oily coatings are difficult to meet GB's VOC control requirements.
[0003] The existing coatings have unstable adhesion on magnesium alloy substrates and are prone to paint peeling and blistering during environmental testing. In addition, the hardness, chemical resistance, and wear resistance of the two-component hydroxylated acrylic polyurethane coatings currently on the market are difficult to meet the requirements of current notebook terminal manufacturers.
[0004] The existing technology mainly uses plasma surface treatment, adjusts the solubility and volatilization rate of the solvent, and adjusts the matching of the primer and the topcoat to improve the adhesion of the paint film on the magnesium alloy substrate. However, plasma surface treatment cannot effectively increase the adhesion of the paint film. The method of adjusting the solubility and volatilization rate of the solvent is mainly an organic solvent system. As the requirements for environmental protection become higher and higher, the existing oily coatings are difficult to meet the GB's control requirements for VOC and cannot effectively meet the requirements of environmental protection. The topcoat in the coating in the existing technology is generally a polyurethane topcoat, and one of the components forming the polyurethane is an acrylic resin. However, the alkali resistance of the acrylic resin is poor. In order to increase the adhesion of the film layer and its alkali resistance, the existing technology mainly adjusts the matching of the primer and the topcoat. Generally, polymers with special structures are selected in primer and topcoat to work with other additives to form a dense and highly adhesive coating. Although the adhesion of the film layer can be increased, the improvement in the alkali resistance of the film layer is not very significant. More importantly, the formed film layer cannot meet the hardness requirements of the notebook shell (magnesium alloy material); further, in order to increase the hardness, the existing methods mainly use fillers or reinforcing agents that can chemically react or physically act with the resin or other components in the coating to increase the hardness of the coating. However, these fillers and reinforcing agents are usually inorganic components. When increasing their hardness, the workability of the coating will be affected, and the toughness of the coating will be seriously affected, making it difficult to achieve a balance between hardness and flexibility.
[0005] Therefore, there is an urgent need for a new water-based coating composition that has excellent adhesion, hardness and weather resistance and can meet the requirements of the notebook shell (magnesium alloy material) for the coating film. Summary of the invention
[0006] The object of the present invention is to provide a waterborne coating composition having excellent adhesion, hardness and weather resistance.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The first aspect of the present invention provides a water-based coating composition, comprising a water-based acrylic polyurethane topcoat and a water-based epoxy primer; the water-based acrylic polyurethane topcoat comprises: component A and component B; the water-based epoxy primer comprises component A and component B; the component A comprises, by weight: 40-70 parts of a water-based hydroxy acrylic dispersion, 0-20 parts of a color paste, 0-5 parts of silicon dioxide, 3-10 parts of a solvent A, 0.1-0.5 parts of a pH regulator, 0.5-1 parts of a wetting agent A, 0.1-0.5 parts of a defoamer A, 3-5 parts of polytetrafluoroethylene wax, 0.5-1 parts of a thickener A, 1-2 parts of an anti-settling agent A, and 5-15 parts of water; In parts by weight, the component B comprises: 65-80 parts of hydrophilic aliphatic polyisocyanate based on hexamethylene diisocyanate, 20-35 parts of propylene glycol methyl ether acetate, and 1-5 parts of a dehydrating agent; in parts by weight, the component A comprises: 40-70 parts of an aqueous epoxy emulsion, 0-5 parts of carbon black, 0-15 parts of titanium dioxide, 2-6 parts of a dispersant, 3-10 parts of a solvent B, 0.5-1 parts of a wetting agent B, 0.1-0.5 parts of a defoaming agent B, 0.5-1 parts of a thickener B, 1-2 parts of an anti-settling agent B, and 5-15 parts of water; in parts by weight, the component B comprises: 55-60 parts of a modified aliphatic amine curing agent and 40-45 parts of water.
[0009] Furthermore, the component A comprises, by weight: 50-60 parts of aqueous hydroxy acrylic dispersion, 12-15 parts of color paste, 2-3 parts of silicon dioxide, 4-6 parts of solvent A, 0.3-0.4 parts of pH adjuster, 0.5-0.8 parts of wetting agent A, 0.2-0.3 parts of defoamer A, 3-5 parts of polytetrafluoroethylene wax, 0.5-0.8 parts of thickener A, 1.5-2 parts of anti-settling agent A, and 8-12 parts of water; the component B comprises, by weight: 70 parts of hydrophilic aliphatic polyisocyanate based on hexamethylene diisocyanate -75 parts, propylene glycol methyl ether acetate 25-30 parts, dehydrating agent 3-4 parts; by weight, the component A includes: 55-60 parts of water-based epoxy emulsion, 2-3 parts of carbon black, 5-8 parts of titanium dioxide, 3-4 parts of dispersant, 5-7 parts of solvent B, 0.6-0.8 parts of wetting agent B, 0.3-0.4 parts of defoaming agent B, 0.6-0.8 parts of thickener B, 1.3-1.5 parts of anti-settling agent B, and 8-12 parts of water; by weight, the component B includes: 55-60 parts of modified aliphatic amine curing agent and 40-45 parts of water.
[0010] Furthermore, in parts by weight, the component A comprises: 55 parts of water-based hydroxy acrylic dispersion, 15 parts of color paste, 2.5 parts of silicon dioxide, 5 parts of solvent A, 0.4 parts of pH regulator, 0.6 parts of wetting agent A, 0.25 parts of defoamer A, 4 parts of polytetrafluoroethylene wax, 0.65 parts of thickener A, 1.8 parts of anti-settling agent A, and 10 parts of water; in parts by weight, the component B comprises: a hydrophilic aliphatic polyisocyanate based on hexamethylene diisocyanate; 70 parts of ester, 30 parts of propylene glycol methyl ether acetate, and 3.4 parts of dehydrating agent; by weight, the component A includes: 58 parts of water-based epoxy emulsion, 2.5 parts of carbon black, 6 parts of titanium dioxide, 3.5 parts of dispersant, 6 parts of solvent B, 0.65 parts of wetting agent B, 0.35 parts of defoaming agent B, 0.65 parts of thickener B, 1.35 parts of anti-settling agent B, and 10 parts of water; by weight, the component B includes: 60 parts of modified aliphatic amine curing agent and 40 parts of water.
[0011] Furthermore, the hydroxyl content of the aqueous hydroxylated acrylic dispersion is 2.6-3.3%, preferably 3.3%.
[0012] The hydroxyl content of the aqueous hydroxy acrylic dispersion in the present invention is based on the solid content.
[0013] The aqueous hydroxylated acrylic dispersion of the present invention can be obtained commercially, for example, the aqueous hydroxylated acrylic dispersion of model number Wanhua Antkote 2057 has a hydroxyl content of 2.5%, and the aqueous hydroxylated acrylic dispersion of model number Wanhua Antkote 2032 has a hydroxyl content of 3.3%.
[0014] In the present invention, after a lot of research, it was found that the use of an aqueous hydroxyl acrylic dispersion with a specific hydroxyl content can obtain a coating with excellent adhesion, alkali resistance, moisture and heat resistance and high hardness. It is speculated that this is because the use of an aqueous hydroxyl acrylic dispersion with this hydroxyl content in the system of the present invention can make the topcoat have better leveling. When its content is too high, it causes the viscosity of the system to increase, which reduces its leveling, thereby affecting the adhesion of the coating and reducing the alkali resistance and moisture and heat resistance. When its content is too low, it affects the crosslinking density of the coating surface, and cannot chemically wrap the specific aqueous aluminum silver paste in the present invention well, thereby affecting its hardness, alkali resistance and moisture and heat resistance.
[0015] In the present invention, a color paste can be added as needed. In order to enable the composition of the present invention to form a coating film with metallic luster when used, the color paste further includes a double-layer coated water-based aluminum silver paste.
[0016] The system of the present invention belongs to a water-based system. The use of water-based aluminum-silver paste not only has better environmental protection, but also can further increase the dispersion of the water-based aluminum-silver paste in the system of the present invention.
[0017] Furthermore, the preparation method of the double-layer coated water-based aluminum-silver paste is:
[0018] (1) mixing an inorganic silicon-coated water-based aluminum silver paste, n-hexadecane, butoxyethyl acrylate and methyl 3-(4-(1H-imidazole-1-yl)phenyl)acrylate, then adding methyl methacrylate, isooctyl acrylate and azobisisoheptonitrile to mix, and finally adding sodium dodecyl sulfate and water to emulsify at 45-50° C. for 20-30 minutes to obtain an emulsion;
[0019] (2) The emulsion is reacted at 75-80° C. for 6-8 hours, then cooled to room temperature, filtered, and the filter cake is dried to obtain a double-layer coated aqueous aluminum silver paste.
[0020] Furthermore, the solid content of the inorganic silicon-coated aqueous aluminum-silver paste is 50-70%, preferably 63-67%.
[0021] Furthermore, the average particle size D50 of the inorganic silicon-coated aqueous aluminum-silver paste is 6-60 um, preferably 17-19 um.
[0022] Furthermore, the inorganic silicon-coated water-based aluminum-silver paste can be obtained commercially. Preferably, the inorganic silicon-coated water-based aluminum-silver paste is purchased from Shandong Yinjian Metal Pigments Co., Ltd., and its model is ZW-9018.
[0023] Furthermore, the weight ratio of the inorganic silicon-coated aqueous aluminum silver paste, n-hexadecane, butoxyethyl acrylate and 3-(4-(1H-imidazole-1-yl)phenyl)methyl acrylate is 100:(1-2):(20-25):(20-25).
[0024] Furthermore, the weight ratio of the inorganic silicon-coated aqueous aluminum silver paste, methyl methacrylate, isooctyl acrylate, azobisisoheptanenitrile, sodium dodecyl sulfate and water is 100:(10-15):(10-15):(5-6):(10-15):(1000-1500).
[0025] In step (1) of the present invention, mixing is a conventional mixing method in the art, and the present invention has no particular limitation as long as the mixing is uniform.
[0026] In the present invention, the inventors have found that the use of the prepared water-based aluminum paste can not only increase the heat resistance and weather resistance, but also increase the toughness of the coating, and it is not easy to crack and fall off when hit by external force. After a large number of experiments, the inventors speculate that it may be because the prepared water-based aluminum paste has a double-layer coating structure, which can be better wrapped by the water-based hydroxy acrylic dispersion, and the outer layer structure of the water-based aluminum paste contains a five-membered ring imidazole structure, which can better increase the heat resistance and medium resistance. At the same time, the outer layer also contains a flexible chain segment provided by butoxyethyl acrylate, which makes the coating have excellent toughness.
[0027] The adhesion of water-based epoxy coatings on magnesium alloy substrates currently on the market is unstable, and problems such as paint peeling and blistering easily occur during environmental testing. Furthermore, the water-based epoxy emulsion is a mixture of a water-based epoxy emulsion A with an epoxy equivalent of 450-550 g / mol and a water-based epoxy emulsion B with an epoxy equivalent of 190-210 g / mol.
[0028] The waterborne epoxy emulsion A in the present invention can be obtained from the market, and preferably its model is STW703A produced by Shanghai Fine Chemicals, and its epoxy equivalent is 500 g / mol.
[0029] The waterborne epoxy emulsion B in the present invention can be obtained from the market, preferably purchased from Shanghai Yuanbang Resin Factory, with a model number of YPWE-403E and an epoxy equivalent of 200 g / mol.
[0030] The epoxy equivalents in the present invention are all based on the solid content in the waterborne epoxy emulsion, and the present invention will not elaborate on this.
[0031] However, the adhesion of water-based epoxy coatings on magnesium alloy substrates on the market is unstable, and they are prone to paint peeling, bubbling and other problems in environmental tests. In addition, the hardness of the two-component polyurethane topcoat is difficult to meet the requirements of notebook terminal manufacturers. The inventors of the present invention have found through research that the use of two water-based epoxy emulsions with different epoxy equivalents can better increase the adhesion of the coating. This may be because the water-based epoxy emulsions with high and low epoxy equivalents can, on the one hand, form chemical bonds with the components in the topcoat, and on the other hand, the synergistic effect of the two can increase the cross-linking density in the cured product, while making the cross-linking network more uniform and able to adhere to the substrate more stably.
[0032] The hexamethylene diisocyanate-based hydrophilic aliphatic polyisocyanate is selected from at least one of hydrophilic aliphatic polyisocyanate curing agent 305, Covestro Bayhydur XP 2547 and isocyanate curing agent CX-8320, preferably Covestro Bayhydur XP 2547.
[0033] The dehydrating agent in the present invention is selected from the curing agent dehydrating agent commonly used in the art. Further, the dehydrating agent is selected from BF5 of Samsung Chemical and / or TI of Bayer.
[0034] Furthermore, the modified aliphatic amine curing agent is selected from EH-226A modified aliphatic amine curing agent and / or EH-451K modified aliphatic amine curing agent, preferably EH-451K modified aliphatic amine curing agent.
[0035] Furthermore, the silicon dioxide is hydrophilic fumed silica.
[0036] Furthermore, the specific surface area of the silicon dioxide is 175-225m 2 / g.
[0037] The silicon dioxide in the present invention can be obtained from commercial sources, such as Tangshan Sanfu K-200R hydrophilic fumed silica, which has a specific surface area of 200 m 2 / g.
[0038] The polytetrafluoroethylene wax in the present invention refers to polyethylene micropowder wax modified by polytetrafluoroethylene. The polytetrafluoroethylene wax has a slippery property and can increase the wear resistance of the coating. Furthermore, the average particle size of the polytetrafluoroethylene wax is 0.1-1 micron, preferably 0.6 micron.
[0039] The polytetrafluoroethylene wax in the present invention can be obtained from the market, preferably Clariant Cer idust micronized wax 9322F, which has an average particle size of 0.6 microns.
[0040] Furthermore, the average particle size of the carbon black is 10-100 nm, preferably 20 nm.
[0041] The carbon black in the present invention can be obtained commercially. Preferably, the carbon black is Mitsubishi Carbon Black MA100.
[0042] Furthermore, the average particle size of the titanium dioxide is 0.1-0.5 micrometers, preferably 0.23 micrometers.
[0043] The titanium dioxide in the present invention can be obtained from the market, and preferably is the Snow Lotus LR-982 rutile titanium dioxide of Longbai Group, which has an average particle size of 0.23 microns.
[0044] Furthermore, the dispersant is selected from Evonik ZETASPERSE 3100 and / or BASF Di spex 4416, preferably Evonik ZETASPERSE 3100.
[0045] Furthermore, the pH regulator is selected from at least one of triethylamine, 2-amino-2-methyl-1-propanol and ammonia water, preferably triethylamine.
[0046] Furthermore, the solvent A and the solvent B are each independently selected from at least one of propylene glycol methyl ether, ethylene glycol butyl ether, ethylene glycol ethyl ether and propylene glycol ethyl ether, preferably propylene glycol methyl ether.
[0047] Furthermore, the wetting agent A and the wetting agent B are each independently selected from at least one of Evonik Surfyno l 440, Sasol NOVELUT ION 390 and BYK-187, preferably Evonik Surfyno l 440.
[0048] Furthermore, the defoamer A and the defoamer B are independently selected from at least one of BYK-019, BioMax Guangdong Standard SF-8093AKY, Digo 825 and Digo 901W, preferably Digo 901W.
[0049] Furthermore, the thickener A and the thickener B are independently selected from acrylic acid associative thickeners, and the preferred model is TH IXOL 53L, a water-based thickener from Cotai.
[0050] Furthermore, the anti-settling agent A and the anti-settling agent B are each independently selected from polyamide wax.
[0051] The polyamide wax in the present invention can be obtained from the market, and its preferred model is Japan Desbaron polyamide wax water-based coating anti-settling agent AQ-600.
[0052] Furthermore, the weight ratio of component A to component B is (2.5-3)1, preferably 2.5:1.
[0053] Furthermore, the weight ratio of component A to component B is (6-8):1, preferably 7.5:1.
[0054] The second aspect of the present invention provides a method for preparing the water-based coating composition of the present invention, the preparation method comprising:
[0055] Preparation of component A: mixing the color paste, defoamer A, silicon dioxide and water and grinding them to a fineness of less than 25 microns, then sequentially adding solvent A, aqueous hydroxy acrylic dispersion, pH adjuster, wetting agent A, anti-settling agent A, polytetrafluoroethylene wax and thickener A to mix to obtain component A;
[0056] Preparation of component B: Propylene glycol methyl ether acetate and a dehydrating agent are mixed in a nitrogen environment, and then a hydrophilic aliphatic polyisocyanate based on hexamethylene diisocyanate is added and mixed to obtain component B;
[0057] Preparation of component A: carbon black, titanium dioxide, dispersant, defoamer B and water are mixed and ground to a fineness of less than 25 microns, and then solvent B, water-based epoxy emulsion, wetting agent B, anti-settling agent B and thickener B are added in sequence to mix to obtain component A;
[0058] Preparation of component B: Mix the modified aliphatic amine curing agent with water to obtain component B.
[0059] The water-based coating composition of the present invention can be used on a magnesium alloy substrate or a PC substrate, preferably on a magnesium alloy substrate.
[0060] When in use, the thickness of the waterborne acrylic polyurethane topcoat is generally 20-25 microns, and the thickness of the primer is generally 15-25 microns.
[0061] The steps of using the composition of the present invention include:
[0062] S1 After component A and component B are evenly mixed, two coats of water-based epoxy primer are sprayed on the magnesium alloy substrate using air. After the construction is completed, the coating dry film thickness is 15-25 microns. It is naturally dried at 15-25℃ for more than 24 hours, or placed at 15-35℃ for 1-2 hours, and then baked at 60-80℃ for 1-2 hours to form a primer coating;
[0063] S2: Evenly mix component A and component B to obtain a water-based acrylic polyurethane topcoat. After the primer coating is completely dry, spray the water-based acrylic polyurethane topcoat. The dry film thickness of the coating is 20-25 microns. After the construction is completed, the dry film thickness of the coating is 15-25 microns. Dry naturally at 15-25°C for more than 24 hours, or place at 15-35°C for 1-2 hours, and then bake at 60-80°C for 1-2 hours to form a topcoat coating.
[0064] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0065] 1. Compared with other coatings at home and abroad that use organic solvents as polymerization media, the present invention uses water as the polymerization medium. The actual product VOC content is about 200g / L, which is much lower than the control requirements of GB30981-2020 for water-based electronic and electrical primer coatings (420g / L). The production cost is low and it is safe and environmentally friendly.
[0066] 2. The primer in the present invention is cross-linked and cured on the magnesium alloy substrate to form a continuous, complete, uniform, and densely bonded film layer; the topcoat has an excellent cross-linking density on the coating surface, which can meet the performance requirements required by the terminal manufacturers, and retains a good aluminum powder arrangement effect and the recoating performance of the coating. The topcoat and the primer work together to increase the adhesion and alkali resistance of the coating.
[0067] 3. The present invention uses aluminum-silver paste with double-layer coating treatment and acrylic resin with high hydroxyl content that has good coating performance for aluminum powder, which can not only obtain good alkali resistance of the coating film, but also have a very small color difference value △E≤1.5 in the alkali resistance test, thereby solving the pain point problem of alkali-resistant discoloration of water-based two-component silver coating, and can also increase the hardness of the film layer while making the film layer have excellent toughness.
[0068] 4. The present invention uses a modified aliphatic amine curing agent, which has a longer construction time and an activation period of more than 4 hours compared to the commonly used water-based two-component epoxy system on the market. DETAILED DESCRIPTION
[0069] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0070] Example 1
[0071] This embodiment provides a water-based coating composition; including a water-based acrylic polyurethane topcoat and a water-based epoxy primer; the water-based acrylic polyurethane topcoat includes: component A and component B; the water-based epoxy primer includes component A and component B;
[0072] In parts by weight, the component A includes: 55 parts of water-based hydroxy acrylic dispersion, 15 parts of color paste, 2.5 parts of silicon dioxide, 5 parts of solvent A, 0.4 parts of pH adjuster, 0.6 parts of wetting agent A, 0.25 parts of defoamer A, 4 parts of polytetrafluoroethylene wax, 0.65 parts of thickener A, 1.8 parts of anti-settling agent A, and 10 parts of water;
[0073] In parts by weight, the component B comprises: 70 parts of hydrophilic aliphatic polyisocyanate based on hexamethylene diisocyanate, 30 parts of propylene glycol methyl ether acetate, and 3.4 parts of a dehydrating agent;
[0074] In parts by weight, the component A includes: 58 parts of waterborne epoxy emulsion, 2.5 parts of carbon black, 6 parts of titanium dioxide, 3.5 parts of dispersant, 6 parts of solvent B, 0.65 parts of wetting agent B, 0.35 parts of defoaming agent B, 0.65 parts of thickener B, 1.35 parts of anti-settling agent B, and 10 parts of water;
[0075] In parts by weight, the component B includes: 60 parts of modified aliphatic amine curing agent and 40 parts of water;
[0076] The model of the water-based hydroxylated acrylic dispersion is Wanhua Antkote 2032 water-based hydroxylated acrylic dispersion, and its hydroxyl content is 3.3%;
[0077] The color paste is a double-layer coated water-based aluminum paste. The preparation method of the double-layer coated water-based aluminum paste is as follows: (1) mixing inorganic silicon coated water-based aluminum paste, n-hexadecane, butoxyethyl acrylate and 3-(4-(1H-imidazole-1-yl)phenyl) methyl acrylate, then adding methyl methacrylate, isooctyl acrylate and azobisisoheptonitrile to mix, and finally adding sodium dodecyl sulfate and water to emulsify at 45° C. for 25 minutes to obtain an emulsion; (2) reacting the emulsion at 80° C. for 7 hours, then cooling to room temperature, filtering, and drying the filter cake to obtain a double-layer coated water-based aluminum paste;
[0078] The inorganic silicon-coated water-based aluminum silver paste was purchased from Shandong Yinjian Metal Pigment Co., Ltd., with a model of ZW-9018, a solid content of 65%, and an average particle size D50 of 18 μm; the weight ratio of the inorganic silicon-coated water-based aluminum silver paste, n-hexadecane, butoxyethyl acrylate and 3-(4-(1H-imidazole-1-yl)phenyl)methyl acrylate was 100:1.5:23:22; the weight ratio of the inorganic silicon-coated water-based aluminum silver paste, methyl methacrylate, isooctyl acrylate, azobisisoheptonitrile, sodium dodecyl sulfate and water was 100:12:13:5:12:1200;
[0079] The water-based epoxy emulsion is a mixture of a water-based epoxy emulsion A with an epoxy equivalent of 500 g / mol and a water-based epoxy emulsion B with an epoxy equivalent of 200 g / mol; the model of the water-based epoxy emulsion A is STW703A produced by Shanghai Fine Chemicals; the model of the water-based epoxy emulsion B is YPWE-403E produced by Shanghai Yuanbang Resin Factory;
[0080] The hydrophilic aliphatic polyisocyanate based on hexamethylene diisocyanate is Bayhydur XP2547 from Covestro;
[0081] The dehydrating agent is selected from BF5 of Samsung Chemical;
[0082] The modified aliphatic amine curing agent is modified aliphatic amine curing agent EH-451K;
[0083] The silica is Tangshan Sanfu K-200R hydrophilic fumed silica with a specific surface area of 200m 2 / g;
[0084] The polytetrafluoroethylene wax is Clariant Ce i dust micronized wax 9322F, with an average particle size of 0.6 μm;
[0085] The carbon black is Mitsubishi carbon black MA100 with an average particle size of 20 nm;
[0086] The titanium dioxide is Longbai Group’s Snow Lotus LR-982 rutile titanium dioxide, with an average particle size of 0.23 μm;
[0087] The dispersant was Evonik’s ZETASPERSE 3100;
[0088] The pH regulator is triethylamine;
[0089] Solvent A and solvent B are both propylene glycol methyl ether;
[0090] Wetting agent A and wetting agent B are both Evonik Surfyno l 440;
[0091] Defoamer A and defoamer B are both Digo 901W;
[0092] Thickener A and thickener B are both Gaotai water-based thickener TH IXOL 53L;
[0093] Anti-settling agent A and anti-settling agent B are both Japanese Desbaron polyamide wax water-based coating anti-settling agent AQ-600;
[0094] The preparation method of the water-based coating composition comprises:
[0095] Preparation of component A: mixing the color paste, defoamer A, silicon dioxide and water and grinding them to a fineness of less than 25 microns, then sequentially adding solvent A, aqueous hydroxy acrylic dispersion, pH adjuster, wetting agent A, anti-settling agent A, polytetrafluoroethylene wax and thickener A to mix to obtain component A;
[0096] Preparation of component B: Propylene glycol methyl ether acetate and a dehydrating agent are mixed in a nitrogen environment, and then a hydrophilic aliphatic polyisocyanate based on hexamethylene diisocyanate is added and mixed to obtain component B;
[0097] Preparation of component A: carbon black, titanium dioxide, dispersant, defoamer B and water are mixed and ground to a fineness of less than 25 microns, and then solvent B, water-based epoxy emulsion, wetting agent B, anti-settling agent B and thickener B are added in sequence to mix to obtain component A;
[0098] Preparation of component B: Mix the modified aliphatic amine curing agent with water to obtain component B.
[0099] Example 2
[0100] This embodiment provides a water-based coating composition; including a water-based acrylic polyurethane topcoat and a water-based epoxy primer; the water-based acrylic polyurethane topcoat includes: component A and component B; the water-based epoxy primer includes component A and component B;
[0101] Component A includes, by weight: 60 parts of water-based hydroxy acrylic dispersion, 12 parts of color paste, 2 parts of silicon dioxide, 6 parts of solvent A, 0.4 parts of pH adjuster, 0.8 parts of wetting agent A, 0.3 parts of defoamer A, 5 parts of polytetrafluoroethylene wax, 0.5 parts of thickener A, 1.5 parts of anti-settling agent A, and 8 parts of water;
[0102] In parts by weight, the component B comprises: 75 parts of hydrophilic aliphatic polyisocyanate based on hexamethylene diisocyanate, 25 parts of propylene glycol methyl ether acetate, and 4 parts of a dehydrating agent;
[0103] In parts by weight, the component A includes: 60 parts of waterborne epoxy emulsion, 3 parts of carbon black, 5 parts of titanium dioxide, 3 parts of dispersant, 7 parts of solvent B, 0.8 parts of wetting agent B, 0.4 parts of defoaming agent B, 0.8 parts of thickener B, 1.5 parts of anti-settling agent B, and 12 parts of water;
[0104] In parts by weight, the component B includes: 60 parts of modified aliphatic amine curing agent and 40 parts of water;
[0105] The model of the water-based hydroxylated acrylic dispersion is Wanhua Antkote 2057 water-based hydroxylated acrylic dispersion, and its hydroxyl content is 2.6%;
[0106] The color paste is a double-layer coated water-based aluminum paste. The preparation method of the double-layer coated water-based aluminum paste is as follows: (1) mixing inorganic silicon coated water-based aluminum paste, n-hexadecane, butoxyethyl acrylate and 3-(4-(1H-imidazole-1-yl)phenyl) methyl acrylate, then adding methyl methacrylate, isooctyl acrylate and azobisisoheptanenitrile to mix, and finally adding sodium dodecyl sulfate and water to emulsify at 50° C. for 30 minutes to obtain an emulsion; (2) reacting the emulsion at 80° C. for 6 hours, then cooling to room temperature, filtering, and drying the filter cake to obtain a double-layer coated water-based aluminum paste;
[0107] The inorganic silicon-coated water-based aluminum silver paste was purchased from Shandong Yinjian Metal Pigment Co., Ltd., with a model of ZW-9018, a solid content of 65%, and an average particle size D50 of 18 μm; the weight ratio of the inorganic silicon-coated water-based aluminum silver paste, n-hexadecane, butoxyethyl acrylate and 3-(4-(1H-imidazole-1-yl)phenyl)methyl acrylate was 100:2:25:20; the weight ratio of the inorganic silicon-coated water-based aluminum silver paste, methyl methacrylate, isooctyl acrylate, azobisisoheptonitrile, sodium dodecyl sulfate and water was 100:15:15:5:15:1500;
[0108] The water-based epoxy emulsion is a mixture of a water-based epoxy emulsion A with an epoxy equivalent of 500 g / mol and a water-based epoxy emulsion B with an epoxy equivalent of 200 g / mol; the model of the water-based epoxy emulsion A is STW703A produced by Shanghai Fine Chemicals; the model of the water-based epoxy emulsion B is YPWE-403E produced by Shanghai Yuanbang Resin Factory;
[0109] The hydrophilic aliphatic polyisocyanate based on hexamethylene diisocyanate is Bayhydur XP2547 from Covestro;
[0110] The dehydrating agent is selected from Bayer's TI
[0111] The modified aliphatic amine curing agent is modified aliphatic amine curing agent EH-451K;
[0112] The silica is Tangshan Sanfu K-200R hydrophilic fumed silica with a specific surface area of 200m 2 / g;
[0113] The polytetrafluoroethylene wax is Clariant Ce i dust micronized wax 9322F, with an average particle size of 0.6 μm;
[0114] The carbon black is Mitsubishi carbon black MA100 with an average particle size of 20 nm;
[0115] The titanium dioxide is Longbai Group’s Snow Lotus LR-982 rutile titanium dioxide, with an average particle size of 0.23 μm;
[0116] The dispersant was Evonik’s ZETASPERSE 3100;
[0117] The pH regulator is triethylamine;
[0118] Solvent A and solvent B are both propylene glycol methyl ether;
[0119] Wetting agent A and wetting agent B are both Evonik Surfyno l 440;
[0120] Defoamer A and defoamer B are both Digo 901W;
[0121] Thickener A and thickener B are both Gaotai water-based thickener TH IXOL 53L;
[0122] Anti-settling agent A and anti-settling agent B are both Japanese Desbaron polyamide wax water-based coating anti-settling agent AQ-600;
[0123] The preparation method of the water-based coating composition comprises:
[0124] Preparation of component A: mixing the color paste, defoamer A, silicon dioxide and water and grinding them to a fineness of less than 25 microns, then sequentially adding solvent A, aqueous hydroxy acrylic dispersion, pH adjuster, wetting agent A, anti-settling agent A, polytetrafluoroethylene wax and thickener A to mix to obtain component A;
[0125] Preparation of component B: Propylene glycol methyl ether acetate and a dehydrating agent are mixed in a nitrogen environment, and then a hydrophilic aliphatic polyisocyanate based on hexamethylene diisocyanate is added and mixed to obtain component B;
[0126] Preparation of component A: carbon black, titanium dioxide, dispersant, defoamer B and water are mixed and ground to a fineness of less than 25 microns, and then solvent B, water-based epoxy emulsion, wetting agent B, anti-settling agent B and thickener B are added in sequence to mix to obtain component A;
[0127] Preparation of component B: Mix the modified aliphatic amine curing agent with water to obtain component B.
[0128] Comparative Example 1
[0129] The difference between this comparative example and Example 1 is that all 3-(4-(1H-imidazol-1-yl)phenyl)methyl acrylate is replaced by butoxyethyl acrylate.
[0130] Comparative Example 2
[0131] The difference between this comparative example and Example 1 is that all butoxyethyl acrylate is replaced by methyl 3-(4-(1H-imidazol-1-yl)phenyl)acrylate.
[0132] Comparative Example 3
[0133] The difference between this comparative example and Example 1 is that the aqueous epoxy emulsions are all aqueous epoxy emulsions B with an epoxy equivalent of 200 g / mol, that is, there is no aqueous epoxy emulsion A with an epoxy equivalent of 500 g / mol.
[0134] Comparative Example 4
[0135] The difference between this comparative example and Example 1 is that the aqueous epoxy emulsions are all aqueous epoxy emulsions A with an epoxy equivalent of 500 g / mol, that is, there is no aqueous epoxy emulsion B with an epoxy equivalent of 200 g / mol.
[0136] Comparative Example 5
[0137] The difference between this comparative example and Example 1 is that the model of the water-based hydroxy acrylic dispersion is Wanhua Antkote 2025, and the hydroxyl content thereof is 2.0%.
[0138] Comparative Example 6
[0139] The difference between this comparative example and Example 1 is that the model of the water-based hydroxy acrylic dispersion is Wanhua ANTKOTE2042N, and its hydroxyl content is 4.2%.
[0140] Performance Testing
[0141] Preparation of coating samples:
[0142] S1: Component A and component B in the embodiment and the comparative example are mixed evenly, and then two coats of water-based epoxy primer are sprayed on the magnesium alloy substrate using air. After the construction is completed, the coating has a dry film thickness of 15-25 μm, and is naturally dried at 15-25° C. for more than 24 hours, or placed at 15-35° C. for 1-2 hours, and then baked at a temperature of 60-80° C. for 1-2 hours to form a primer coating;
[0143] S2: Component A and component B in the embodiment and the comparative example are mixed evenly to obtain a water-based acrylic polyurethane topcoat. After the primer coating is completely dry, the water-based acrylic polyurethane topcoat is sprayed. The coating dry film thickness is 20-25 microns. After the construction is completed, the coating dry film thickness is 15-25 microns. It is naturally dried at 15-25°C for more than 24 hours, or first placed at 15-35°C for 1-2 hours, and then baked at a temperature of 60-80°C for 1-2 hours to form a coating film.
[0144] 1. Impact resistance test: The impact resistance of the coating is tested in accordance with GB / T 1732-1993. The maximum height (cm) at which a 1kg weight falls on the surface of the sample without causing damage is 50cm or higher for Class A; less than 50cm and greater than or equal to 35cm for Class B; less than or equal to 35cm for Class C.
[0145] 2. Alkali resistance test: Soak the sample coated with the coating in 0.1 mol / L NaOH aqueous solution at 70°C for 48 hours. If the coating does not change color, fall off, crack or bubble, it is qualified, otherwise it is unqualified.
[0146] 3. Moisture and heat resistance test: Place the sample coated with the coating in an environment of 90℃*95%RH for 150h. If the coating does not change color, fall off, crack or bubble, it is qualified; otherwise, it is unqualified.
[0147] 4. Hardness test: Use a drawing pencil scratch tester to test according to the national standard GB / T 6739-2006.
[0148] 5. Adhesion test: Adopt the hundred grid method and test according to GB / T 9286-1998.
[0149] The test results are shown in Table 1.
[0150] Table 1 Performance test results
[0151] Impact resistance Alkali resistance Heat and humidity resistance hardness Adhesion Example 1 60cm qualified qualified 3H 5B Example 2 56cm qualified qualified 3H 5B Comparative Example 1 54cm Failure Failure 2H 5B Comparative Example 2 38cm qualified qualified 3H 5B Comparative Example 3 44cm Failure Failure 3H 4B Comparative Example 4 51cm Failure Failure 2H 4B Comparative Example 5 53cm Failure Failure 2H 5B Comparative Example 6 50cm Failure Failure 3H 4B
[0152] It can be seen from the above performance test results that Examples 1-2 have excellent adhesion, alkali resistance, moisture and heat resistance, and hardness, especially Example 1 has better comprehensive performance. According to the experimental results, it is speculated that this is because the water-based epoxy coating in the present invention can, on the one hand, be chemically bonded with the components in the topcoat, and on the other hand, the synergistic effect of the two can increase the crosslinking density in the cured product, while making the crosslinking network more uniform and able to more stably adhere to the substrate. The synergistic effect of the various components in the topcoat can better chemically wrap the specific water-based aluminum silver paste in the present invention, thereby increasing the hardness, alkali resistance, and moisture and heat resistance of the coating.
[0153] However, the comparative examples were significantly inferior to the embodiments in the corresponding performance tests because they did not adopt the necessary technical solutions. In comparative example 1, the water-based aluminum paste prepared by not using the raw materials containing 4-imidazole acrylic acid was unqualified in terms of moisture and heat resistance and alkali resistance, which proved that the water-based aluminum paste prepared by using 4-imidazole acrylic acid had an important influence on the moisture and heat resistance and alkali resistance of the paint film prepared by the composition; in comparative example 2, the water-based aluminum paste prepared by not using butoxyethyl acrylate reduced the impact resistance, i.e., the toughness, of the paint film prepared by the composition, which proved that the water-based aluminum paste prepared by using butoxyethyl acrylate had a certain influence on the toughness of the composition; in comparative example 3, the water-based epoxy emulsion A with an epoxy equivalent of 450-550 g / mol was not used, and in comparative example 4, the water-based epoxy emulsion B with an epoxy equivalent of 190-210 g / mol was not used, which would affect the adhesion of the coating and further reduce its alkali resistance and moisture and heat resistance, which proved that in the overall scheme of the present invention, 450-550 g / mol The aqueous epoxy emulsion A of 100-210 g / mol has a synergistic effect with the aqueous epoxy emulsion B of 190-210 g / mol; in Comparative Example 5, an aqueous hydroxyl acrylic dispersion with a hydroxyl content lower than the preferred content of the present invention is used, and its alkali resistance and hardness are unqualified; in Comparative Example 6, an aqueous hydroxyl acrylic dispersion with a hydroxyl content higher than the preferred content of the present invention is used, and its adhesion is reduced, resulting in unqualified alkali resistance and moisture and heat resistance, which proves that in the overall scheme of the present invention, it is necessary to use an aqueous hydroxyl acrylic dispersion within a specific hydroxyl value range to achieve excellent adhesion, alkali resistance, moisture and heat resistance.
[0154] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A water-based coating composition, characterized in that: Includes water-based acrylic polyurethane topcoat and water-based epoxy primer; The waterborne acrylic polyurethane topcoat comprises: component A and component B; the waterborne epoxy primer comprises component A and component B; the component A comprises, by weight, 50-60 parts of waterborne hydroxyl acrylic dispersion, 12-15 parts of color paste, 2-3 parts of silicon dioxide, 4-6 parts of solvent A, 0.3-0.4 parts of pH regulator, 0.5-0.8 parts of wetting agent A, 0.2-0.3 parts of defoamer A, 3-5 parts of polytetrafluoroethylene wax, 0.5-0.8 parts of thickener A, 1.5-2 parts of anti-settling agent A, and 8-12 parts of water; the component B comprises, by weight, a hexamethylene dimethicone-based 70-75 parts of hydrophilic aliphatic polyisocyanate of isocyanate, 25-30 parts of propylene glycol methyl ether acetate, and 3-4 parts of dehydrating agent; by weight, the component A includes: 55-60 parts of waterborne epoxy emulsion, 2-3 parts of carbon black, 5-8 parts of titanium dioxide, 3-4 parts of dispersant, 5-7 parts of solvent B, 0.6-0.8 parts of wetting agent B, 0.3-0.4 parts of defoaming agent B, 0.6-0.8 parts of thickener B, 1.3-1.5 parts of anti-settling agent B, and 8-12 parts of water; by weight, the component B includes: 55-60 parts of modified aliphatic amine curing agent and 40-45 parts of water; Wherein, the hydroxyl content of the aqueous hydroxylated acrylic dispersion is 2.6-3.3%; The color paste includes a double-layer coated water-based aluminum paste; the preparation method of the double-layer coated water-based aluminum paste is as follows: (1) mixing inorganic silicon coated water-based aluminum paste, n-hexadecane, butoxyethyl acrylate and 3-(4-(1H-imidazole-1-yl)phenyl) methyl acrylate, then adding methyl methacrylate, isooctyl acrylate and azobisisoheptonitrile to mix, and finally adding sodium dodecyl sulfate and water to emulsify at 45-50°C for 20-30 minutes to obtain an emulsion; (2) reacting the emulsion at 75-80°C for 6-8 hours, then cooling to room temperature, filtering, and drying the filter cake to obtain a double-layer coated water-based aluminum paste.
2. The water-based coating composition according to claim 1, characterized in that: The solid content of the inorganic silicon-coated water-based aluminum-silver paste is 50-70%; the average particle size D50 of the inorganic silicon-coated water-based aluminum-silver paste is 6-60 μm.
3. The aqueous coating composition according to claim 2, characterized in that: The weight ratio of the inorganic silicon-coated water-based aluminum paste, n-hexadecane, butoxyethyl acrylate and 3-(4-(1H-imidazole-1-yl)phenyl)methyl acrylate is 100:(1-2):(20-25):(20-25); the weight ratio of the inorganic silicon-coated water-based aluminum paste, methyl methacrylate, isooctyl acrylate, azobisisoheptonitrile, sodium dodecyl sulfate and water is 100:(10-15):(10-15):(5-6):(10-15):(1000-1500.
4. The aqueous coating composition according to any one of claims 1 to 3, characterized in that: The water-based epoxy emulsion is a mixture of a water-based epoxy emulsion A with an epoxy equivalent of 450-550 g / mol and a water-based epoxy emulsion B with an epoxy equivalent of 190-210 g / mol.
5. The aqueous coating composition according to any one of claims 1 to 3, characterized in that: The hydrophilic aliphatic polyisocyanate based on hexamethylene diisocyanate is selected from at least one of hydrophilic aliphatic polyisocyanate curing agent 305, Covestro Bayhydur XP 2547 and isocyanate curing agent CX-8320; the dehydrating agent is selected from BF5 of Samsung Chemical and / or TI of Bayer; the modified aliphatic amine curing agent is selected from EDICO modified aliphatic amine curing agent EH-226A and / or modified aliphatic amine curing agent EH-451K; the dispersant is selected from Evonik ZETASPERSE 3100 and / or BASF Dispex® 4416; the pH adjuster is selected from at least one of triethylamine, 2-amino-2-methyl-1-propanol and ammonia water.
6. The aqueous coating composition according to any one of claims 1 to 3, characterized in that: The solvent A and the solvent B are each independently selected from at least one of propylene glycol methyl ether, ethylene glycol butyl ether, ethylene glycol ethyl ether and propylene glycol ethyl ether; the wetting agent A and the wetting agent B are each independently selected from at least one of Evonik Surfynol 440, Sasol NOVELUTION 390 and BYK-187; the defoamer A and the defoamer B are each independently selected from at least one of BYK-019, BioMax Guangdong Biaomei SF-8093AKY, Digo 825 and Digo 901W; the thickener A and the thickener B are each independently selected from acrylic acid associative thickeners; the anti-settling agent A and the anti-settling agent B are each independently selected from polyamide wax.
7. The aqueous coating composition according to any one of claims 1 to 3, characterized in that: The weight ratio of component A to component B is (2.5-3):1; the weight ratio of component A to component B is (6-8):
1.
8. A method for preparing the water-based coating composition according to any one of claims 1 to 7, characterized in that: The preparation method comprises: Preparation of component A: mixing the color paste, defoamer A, silicon dioxide and water and grinding them to a fineness of less than 25 microns, then sequentially adding solvent A, aqueous hydroxy acrylic dispersion, pH adjuster, wetting agent A, anti-settling agent A, polytetrafluoroethylene wax and thickener A to mix to obtain component A; Preparation of component B: Propylene glycol methyl ether acetate and a dehydrating agent are mixed in a nitrogen environment, and then a hydrophilic aliphatic polyisocyanate based on hexamethylene diisocyanate is added and mixed to obtain component B; Preparation of component A: carbon black, titanium dioxide, dispersant, defoamer B and water are mixed and ground to a fineness of less than 25 microns, and then solvent B, water-based epoxy emulsion, wetting agent B, anti-settling agent B and thickener B are added in sequence to mix to obtain component A; Preparation of component B: Mix the modified aliphatic amine curing agent with water to obtain component B.
Citation Information
Patent Citations
Water-based epoxy low-zinc primer and preparation method thereof
CN111718636A
Multicolor low-gloss water-based paint primer-finish composition for passenger train
CN113201272A
Water-based double-component matched paint as well as preparation method and application thereof
CN115368805A
Waterborne epoxy / polyurethane composite coating for engineering machinery and preparation method of waterborne epoxy / polyurethane composite coating
CN118291008A
Water-based radiation refrigeration coating for metal surface, preparation method of water-based radiation refrigeration coating and coating
CN118325420A